2007
DOI: 10.1016/j.juro.2007.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bone Turnover Markers (PINP and ICTP) for the Early Detection of Bone Metastases in Patients With Prostate Cancer: A Longitudinal Approach

Abstract: Followup measurement of serum PINP and ICTP is useful in the early assessment of skeletal metastases in patients with prostate cancer regardless of the confounding role of androgen deprivation treatment. The bone formation marker is the most indicative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 21 publications
0
39
1
1
Order By: Relevance
“…1, were also described in four other studies including patients with osseous metastases in comparison to metastasis-free prostate carcinoma patients [89,[139][140][141]. The same goes for BAP as "the" characteristic formation marker.…”
Section: Bone Markers In Diagnosticsmentioning
confidence: 71%
“…1, were also described in four other studies including patients with osseous metastases in comparison to metastasis-free prostate carcinoma patients [89,[139][140][141]. The same goes for BAP as "the" characteristic formation marker.…”
Section: Bone Markers In Diagnosticsmentioning
confidence: 71%
“…Several biochemical markers of bone formation and resorption with varying specificity and sensitivity are used to predict bone turnover, to diagnose metabolic bone disease, and to monitor antiresorptive treatment and its effectiveness. Several studies have assessed the diagnostic efficacy of both bone formation and resorption markers for detection of bone metastases in PCa [8][9][10]20]. Recently, we reported that serum bone formation markers [total and bone-specific alkaline phosphatase (tALP and BAP)] and bone resorption markers [carboxyterminal telopeptide of type I collagen (1CTP) and tartrateresistant acid phosphatase isoenzyme 5b (TRAP-5b)] levels were reliable in the detection of bone metastatic spread and in predicting survival probability in PCa patients with bone metastasis [11].…”
Section: Discussionmentioning
confidence: 99%
“…This study presents several limitations. This is a retrospective study and some newly described variables could not be investigated such functional index [20] or biological parameters exploring bone turnover [3,5,8,9]. This is a single center study conducted in a medical oncology department with accrual of patients very different from orthopedic and neurosurgical units.…”
Section: Discussionmentioning
confidence: 99%
“…The median number of bone metastasis was 3 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Most of patients experienced biological inflammatory syndrome, the median value of C-reactive protein was 45 mg/l (range, 1-340), whereas the upper limit of normal was set at 6.…”
Section: Patients' Characteristicsmentioning
confidence: 99%